2006
DOI: 10.1038/sj.cr.7310003
|View full text |Cite
|
Sign up to set email alerts
|

The quantal theory of immunity

Abstract: Exactly how the immune system discriminates between all environmental antigens to which it reacts vs. all selfantigens to which it does not, is a principal unanswered question in immunology. As set forth in this review, because of the advances in our understanding of the immune system that have occurred in the last 50 years, for the first time it is possible to formulate a new theory, termed the "Quantal Theory of Immunity", which reduces the problem from the immune system as a whole, to the individual cells c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…It has previously been proposed that a T cell stimulus must exceed a discrete threshold to trigger proliferation (1,30). The IL-2Rα switch found here provides a mechanistic basis for this activation threshold.…”
Section: Discussionmentioning
confidence: 85%
“…It has previously been proposed that a T cell stimulus must exceed a discrete threshold to trigger proliferation (1,30). The IL-2Rα switch found here provides a mechanistic basis for this activation threshold.…”
Section: Discussionmentioning
confidence: 85%
“…To this end, we generated a computational model to compare the potential consequences of the observed binary and a hypothetical graded IL-2 secretion for the adaptive immune response. The model allowed us to simulate the outcome of these different scenarios taking into account quantitative spatial information in the spleen (Busse et al, 2010; Chapman et al, 1981; Lischke et al, 2012; Mueller and Germain, 2009; Sabatos et al, 2008; Smith, 2006). Our model confirmed that Treg cells become activated by IL-2 at lower antigen concentrations than Th cells and predicted that graded IL-2 secretion would result in activation of all T cells in a very narrow range of antigen stimulus, which is represented by a very steep slope of the activation curve of Th and Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…We used flow cytometry to assess the capacity of the new molecule to bind to the CTLL-2 cells. This cell line expresses the highaffinity abg IL-2R just as the activated T cells do, with $5-10-fold excess of the free a-chain (20). For detection of His-tagged recombinant proteins bound to the cell surface, we used a PEconjugated anti-His-tag mAb.…”
Section: Mutein Productionmentioning
confidence: 99%